Error Analysis Of Translated Text Made By Maritime Students (in Maritime Context) - Guritno Aditya Warman (Borneo Educational Journal (Borju), 2019)
Despite its importance, translation is just newly concerned for studies. Maritime students learning Maritime English are often faced with translation activity, especially as a way to introduce new field-specific terms in the learning process. The complex nature of the field has become a challenge to the beginner learners involved in the activity related to the field. The purpose of the study is to investigate the types of error that students often make when translating maritime texts. The participants of the study were 5 maritime students at first year involving in the subject of Maritime English. Instrument utilized in the study was a checklist of translation errors adapted from the theory of Nord (1997). The results indicated that most of translation errors made were related to linguistics translation errors. The conclusion drawn was that the students faced a challenge concerning the lack of English vocabulary, both General English vocabulary and Maritime English terms.